Ali ZJN-2 res prepoveduje naročnikom, da določijo najvišjo ceno, ki so jo pripravljeni plačati za blago - Kranjc, Vesna (Podjetje in delo, 2015)
The author is critical of the decision of the Slovenian National Review Commission No. 018-132/2014-6. The Commission decided that it is against the Public Procurement Act (ZJN-2) if an authority in the contract notice and in the other documents relating to the call far tenders states maximum price for goods, if at the same time the authority does not demonstrate that a reason for the maximum price is its budget ceiling or market conditions. The Commission explained that such requirements come from ZJN-2 rules of unacceptable offer. On the contrary, the author argues that in the discussed case the maximum price is the authority's condition. Such a condition is not discriminatory, it merely meets the needs of the authority and so it is fally consistent with public procurement rules. The article also analyses similar judgement of the ECJ in the case T-8109.
Keywords: cene; javna naročila; javni razpisi; ponudbe; pravna ureditev